ТЕКСТОМЕТРИЈА У КОРПУСНОЈ ЛИНВИСТИЦИ: СРПСКИ ФУДБАЛСКИ КОРПУС срФудКо - Лазаревић, Јелена В. (Nasleđe, 2024)
The corpus srFudKo is the first football corpus of the journalistic genre in Serbian. It represents a partition of the larger FudKo, which is formed by two sections: the Spanish Language corpus esFudKo and the Serbian Language corpus srFudKo, compiled and processed through the unique methodology of textometry in Corpus Linguistics. The aim of the paper is showcasing the formation of srFudKo, analyzing the specificities of the language of football utilized in media articles through statistic and textometric analysis, through the insight into the use of the given tools. The corpus of football articles in srFudKo has been compiled from five Serbian websites: B92, Blic, Mondo, Politika, and Sportklub. It has been prepared as a collection of XML data files, organized by year and website of origin. A total of 11.117 articles were distributed in 37 databases. The domain corpus was processed through tokenization, tagging of the word type and lemmatization. The corpus sr FudKo contains 10.100.553 tokens, out of which 8.618.426 represent words, while 1.482.127 represent interpunction. The average length of an article is 1068 words. The distribution of certain word frequencies in srFudKo testifies to the fact that the Football Corpus contains more proper names and numbers than the Standard Serbian Language Corpus to a significant extent. The specificities of srFudKo are: emoticons of various kinds, as well as different symbols which pertain to the category of corpus word length 1, word length 5 as the most frequent within the corpus, marking a high index of usage specificity of word type in various websites, the uniqueness of concordances and collocations.